First Principle Study of Structural, Electronic, Optical, and Thermodynamic Properties of Scandium-Doped Zirconia Zr1−xScxO2,x=0.125 - Lemessa Asefa Eressa; Zeleke Deressa Gerbi (Advances in Condensed Matter Physics)
The effect of scandium doping on the structural, electronic, optical, and thermodynamic properties of scandium-doped zirconia (Zr0.875Sc0.125 O1.9375) was investigated by first-principles calculations. The results of electronic property calculation show that the incorporation of scandium (Sc3+) in ZrO2 has reduced its bandgap due to the formation of scandium 3d states in the conduction band. The analysis of optical properties shows that scandium doping in ZrO2 improves the real ε1 and imaginary dielectric functions ε2, extinction coefficient (k), refractive index (n), reflectivity (R), and absorption coefficient (α) properties thereby enhancing its photocatalytic and optical activities. The heat capacities of ZrO2 and Sc-ZrO2 calculated at temperature of 800 K are 74.27 and 77.98 J/K/Nmol, respectively. The result of thermodynamic properties calculations show that doping scandium in zirconia enhances its entropy and specific heat capacity thereby allowing it to be thermodynamically stable for a wide range of electronic applications.